Conclusions Drawn from the Study on the Content and Results Obtained Following the External Public Audit Missions Performed by the Court of Auditors in Entities of the Ministry of National Defense in the Last 5 Years - Pilică Marian Claudiu (Scientific Bulletin, 2023)
The research carried out through this article was structured starting from the clarification of some key concepts of external public audit, continuing with revealing the role of the supreme institutions of external public audit (such as the Romanian Court of Auditors) in this action of great importance and complexity and concluding with the practical aspects related to the conclusions drawn by the Court of Auditors in the audit missions of the financial statements performed in recent years in army entities. Thus, the approach was structured on the following chapters: